AFKAR SHOP'S MARKETING COMMUNICATION STRATEGY IN ATTRACTING BUYERS' INTEREST ON FACEBOOK - Yulan Savina; Muhammad Alfikri (LP2M IAI Nazhatut Thullab Sampang, 2022)
Abstract: The purpose of this research is to find out the marketing communication strategy implemented by Afkar Shop in utilizing Facebook social media as a marketing tool to increase buyer interest. This type of research is qualitative research. In this study, researchers used interviews, observation and documentation of Afkar Shop owners. The theory used in this study is positioning theory, which in this study emphasizes how Afkar Shop owners have media that they feel are capable of meeting the needs that support their business. Based on the results of the study it can be concluded that the marketing communication strategy implemented by Afkar Shop through Facebook social media is able to achieve marketing goals and increase sales. The results of this study in terms of positioning, namely Afkar Shop creates the image of